(untitled) (Cadernos de Psicologia Social do Trabalho, 2005)
The article intends to show some ways the unemployed deal with their own conditions. It assume that different contexts and places would allow different ways to deal with unemployment to develop. Therefore, we had semi-prepared interviews in localities where unemployment is an institutional theme professional - employment services - as much as localities where there wasn’t this kind of concern, although there were unemployed people - such as taverns and churches. The interviews intended to establish themes on experienced unemployment through varied dimensions, from the speech of the experience of the unemployed workers, passing through different representations of unemployment in the society. Amongst the established categories of analysis, time emerged remarkably, in several ways, and became consolidated as the main category, making a synthesis of what we found. We considered that, in fact, different expressions about unemployment surfaced at places with different social functions and those activities, together with the individuals’ representations on unemployment, were the axis that shaped the form and subject of the interviews, pointing both similarities and dissimilarities. In this context, we identified three dimensions on the subjects’ speeches as fundamental on their ways of dealing with unemployment: causes of unemployment, emotional existence and critique about the situation.